Mystery of the Roman ransom - Winterfeld, Henry; Biermann, Fritz (New York Harcourt Brace Jovanovich, 1971)
The purchase of a slave for their teacher leads a group of Roman schoolboys into a dangerous intrigue.
Translation of Caius geht ein Licht auf.
Keywords: Mystery and detective stories; Rome -- Fiction